2015
DOI: 10.1152/ajpheart.00485.2014
|View full text |Cite
|
Sign up to set email alerts
|

Early right ventricular fibrosis and reduction in biventricular cardiac reserve in the dystrophin-deficient mdx heart

Abstract: Duchenne muscular dystrophy (DMD) is a progressive disease of striated muscle deterioration. Respiratory and cardiac muscle dysfunction are particularly clinically relevant because they result in the leading causes of death in DMD patients. Despite the clinical and physiological significance of these systems, little has been done to understand the cardiorespiratory interaction in DMD. We show here that prior to the onset of global cardiac dysfunction, dystrophin-deficient mdx mice have increased cardiac fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 74 publications
5
65
0
1
Order By: Relevance
“…Furthermore, these mice have significant reductions in cardiac function (Lu and Hoey 2000; Quinlan et al. 2004; Meyers and Townsend 2015) and significant reductions in respiratory function (Farkas et al. 2007; Ishizaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these mice have significant reductions in cardiac function (Lu and Hoey 2000; Quinlan et al. 2004; Meyers and Townsend 2015) and significant reductions in respiratory function (Farkas et al. 2007; Ishizaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…The group average of the slope was significantly smaller (p = 0.004, Student's t-test) in the mdx RV (20.3 ± 28.4°/mm) than in the BL6 RV (67.9 ± 12.6°/mm). The severe structural remodeling observed in the RV of the 7-month-old mdx mouse is most likely caused by the diaphragm degeneration related pulmonary dysfunction [17,18]. Deterioration of the respiratory function increases pulmonary vascular resistance which then leads to increased RV stress [17].…”
Section: Resultsmentioning
confidence: 99%
“…The severe structural remodeling observed in the RV of the 7-month-old mdx mouse is most likely caused by the diaphragm degeneration related pulmonary dysfunction [17,18]. Deterioration of the respiratory function increases pulmonary vascular resistance which then leads to increased RV stress [17]. This process eventually results in tissue damage in the RV [17,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated a trend toward a decrease with age for LVEF at rest (p = 0.051) but not for RVEF (p = 0.8). A recent study by Meyers et al using a novel biventricular cardiac catheterization technique coupled with cardiac stress testing reported that in dystrophin deficient mdx mice the RV was particularly affected by cardiac fibrosis [22]. Although unstimulated cardiac function was relatively normal, there were significant reductions in RV and LV systolic and diastolic function in response to dobutamine.…”
Section: Discussionmentioning
confidence: 99%